ELEMENTARY PRE-SERVICE TEACHERS’ SELF-EFFICACY IN MATHEMATICS - Darta Darta; Siti Maryam Rohimah; Ahmad Ahmad (AdMathEdu : Jurnal Ilmiah Pendidikan Matematika, Ilmu Matematika dan Matematika Terapan, 2018)
Self-efficacy (SE) is related to someone’s belief influencing their success, including success in teaching mathematics for elementary pre-service teachers. This research aimed to analyse: 1) the self-efficacy difference between high-levelled students and moderate-levelled students; 2) the correlation of self-efficacy indicators; 3) correlation of self-efficacy statements, and 4) pattern interpretation of significant correlation tendency between each self-efficacy statement on elementary pre-service teachers. The subjects of this research were the senior students of Primary Education Department in one of private universities in Bandung. The self-efficacy data were obtained from 149 students. The correlation and mean difference test analysis were done with the support of SPSS. The result showed that the self-efficacy of high-levelled students was better than the self-efficacy of medium-levelled students, there was positive significant correlation either for each self-efficacy indicator or self-efficacy statement. From the correlation, there was a meaningful pattern for self-efficacy of elementary pre-service teachers.